Old and Novel Therapies for Primary Biliary Cirrhosis - Parés, Albert (Seminars in Liver Disease, 2014)
Despite the presumed immunological pathogenesis of primary biliary cirrhosis, no clear or even harmful consequences resulted from some specific treatments addressed to modify the immunological condition. However, ursodeoxycholic acid (UDCA; 13–16 mg/kg/d) has clear favorable effects not only by improving biochemical cholestasis, but also by delaying the histological progression. Long -term treatment with UDCA is associated with excellent survival, free of transplantation in cases showing biochemical response at one year. In the remaining patients, data on the effect of fibrates, budesonide, or obeticholic acid are encouraging. Pruritus is usually managed using resins; further steps are needed in resistant cases with the use of rifampicin, naltrexone, sertraline, or invasive procedures such as albumin dialysis. Osteoporosis, which is highly prevalent in patients with deep and prolonged cholestasis, improves with bisphosphonates; current data indicate that both weekly alendronate and monthly ibandronate increase bone mass in patients with osteoporosis. Nutritional and fat-vitamin supplementation is also mandatory in patients with severe cholestasis.
Keywords: ursodeoxycholic acid; fibrates; budesonide; obeticholic acid; bisphosphonates; pruritus; osteoporosis